PWE-155 Should Patients with Human Immunodeficiency Virus and Gastrointestinal Symptoms be Routinely Tested for Pancreatic Exocrine Insufficiency?. (17th August 2016) - Campbell, JA; Sanders, DS; Hopper, AD
Abstract : Introduction: Diarrhoea and gastrointestinal (GI) symptoms are common symptom in patients with human immunodeficiency virus (HIV). Malabsorption secondary to pancreatic exocrine insufficiency (PEI) has been reported in patients with HIV. Treatment with pancreatic enzyme replacement therapy (PERT) improves symptoms and reduces complications of PEI (malnutrition and osteoporosis). We aimed to calculate the prevalence of PEI in patients with HIV referred to gastroenterology secondary care clinics for persistent GI symptoms. Methods: All patients tested for PEI between 2010 and 2014 were identified. Presenting symptoms and presence of HIV were noted. Faecal elastase (FEL-1) was used to assess pancreatic function with FEL-1 <200μg/g defined as abnormal. Co-morbidities, response to PERT and abdominal imaging results were noted. Prevalence of PEI was compared in patients with and without HIV. Patients treated with PERT were identified on follow up and a positive symptom response noted. Results: 84 patents were identified during the period. 21 were identified with HIV (mean age 47.5, SD 9.8, 85.7% male). 12/21 (57.1%) HIV patients with GI symptoms had low FEL-1 compared to 8/63 (12.7%) patients with GI symptoms without HIV (p =< 0.0001). The most common presenting GI symptom in patients tested for FEL-1 was diarrhoea, (85.7% in both groups) other symptoms included abdominal pain (HIV 9.5%, non HIV 19.0%), weight loss (HIV 0%, control 9.5%) and bloating (HIV 4.8%, control 6.3%). 10/12 (83.3%) HIV patients with low FEL-1 had abdominal imaging. Pancreatic abnormalities were detected in 2/10 cases (20%). 7/8 (87.5%) controls with low FEL-1 had imaging, 3/7 (42.9%) had pancreatic abnormalities. In both groups pancreatic calcification and atrophy were detected. No malignancy was identified. 9/12 (72.5%) HIV patients and 5/8 (62.5%) controls were treated with PERT. 9/9 (100%) HIV patients reported symptomatic improvement; 4/5 (80%) controls derived benefit. Doses prescribed varied from 60, 000–140, 000 units/day across both groups. Conclusion: Given its significantly high yield and response to treatment FEL-1 should be performed to check for PEI in patients with HIV presenting with gastrointestinal symptoms or weight loss. Disclosure of Interest: None Declared